Thermal habitat of adult Atlantic salmon Salmo salar in a warming ocean - Strøm, John Fredrik; Thorstad, Eva Bonsak; Rikardsen, Audun (Journal of Fish Biology, 2019)
The year‐round thermal habitat at sea for adult Atlantic salmon Salmo salar ( n = 49) from northern Norway was investigated using archival tags over a 10 year study period. During their ocean feeding migration, the fish spent 90% of the time in waters with temperatures from 1.6–8.4°C. Daily mean temperatures ranged from −0.5 to 12.9°C, with daily temperature variation up to 9.6°C. Fish experienced the coldest water during winter (November–March) and the greatest thermal range during the first summer at sea (July–August). Trends in sea‐surface temperatures influenced the thermal habitat of salmon during late summer and autumn (August–October), with fish experiencing warmer temperatures in warmer years. This pattern was absent during winter (November–March), when daily mean temperatures ranged from 3.4–5.0°C, in both colder and warmer years. The observations of a constant thermal habitat during winter in both warmer and colder years, may suggest that the ocean distribution of salmon is flexible and that individual migration routes could shift as a response to spatiotemporal alterations of favourable prey fields and ocean temperatures.